Nutrition and hydration of patients in a persistent vegetative state - Lacasella, Giorgia Viola; Karaboue, Karidia (Progress in Nutrition, 2022)
Entering a persistent vegetative state is undoubtedly devastating, as is its temporally unpredictable permanency. However, it is out of the question that the tragic nature of a pathological state such as PVS, however extreme, may in the slightest way alter the dignity of those affected nor their full rights. It is not possible to justify any denial or weakening of the right to care which should be guaranteed as for any other human being. Given the prominent number of people in a persistent vegetative state even in Italy, as well as the ongoing controversy over whether or not nutrition and hydration through a tube or percutaneous enterogastrostomy should be considered medical treatment and/or therapeutic intervention, it seems helpful to reiterate some fundamental bioethical principles.